2005
DOI: 10.1103/physrevb.71.045119
|View full text |Cite
|
Sign up to set email alerts
|

Electronic structure of samarium monopnictides and monochalcogenides

Abstract: The electronic structures of SmX ͑X = N, P, As, Sb, Bi, O, S, Se, Te, Po͒ compounds are calculated using the self-interaction corrected local-spin density approximation. The Sm ion is described with either five or six localized f electrons while the remaining electrons form bands, and the total energies of these scenarios are compared. With five localized f electrons a narrow f band is formed in the vicinity of the Fermi level leading to an effective intermediate valence. This scenario is the ground state of a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
45
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
4
3

Relationship

2
5

Authors

Journals

citations
Cited by 67 publications
(53 citation statements)
references
References 58 publications
8
45
0
Order By: Relevance
“…Because of the different degree of hybridization between the rare-earth band-like f and the nitrogen p states, in the vicinity of the Fermi level, these compounds demonstrate different electronic properties. This is consistent with the electronic structures of SmX (X = N, P, As, Sb, Bi) which have been studied by Svane et al [73]. Svane and co-workers found that the occupied f bands are formed in the vicinity of the Fermi level in all the SmX compounds.…”
Section: Self Interaction Correction (Sic)supporting
confidence: 76%
See 1 more Smart Citation
“…Because of the different degree of hybridization between the rare-earth band-like f and the nitrogen p states, in the vicinity of the Fermi level, these compounds demonstrate different electronic properties. This is consistent with the electronic structures of SmX (X = N, P, As, Sb, Bi) which have been studied by Svane et al [73]. Svane and co-workers found that the occupied f bands are formed in the vicinity of the Fermi level in all the SmX compounds.…”
Section: Self Interaction Correction (Sic)supporting
confidence: 76%
“…Nevertheless, concepts like the Hubbard U and the self-energy Σ are now being widely adopted [73,107]. In addition, the Wannier functions make it possible to set up localized orbitals through a plane wave basis [116,117].…”
Section: Other Theoretical Approachesmentioning
confidence: 99%
“…In this phase the localised f 5 Sm ions coexist with a partly occupied narrow f -band, effectively describing an intermediate valent phase 61 . The calculated and measured transition pressures are listed in Table II.…”
Section: Sm Monopnictides and Monochalcogenidesmentioning
confidence: 99%
“…For these compounds the volume changes continuously, but anomalously, with pressure (at room temperature) 58,59 . From the photoemission studies it is concluded that SmSe and SmTe at amibient pressure, like SmS, are also of predominantly divalent f Figure 5 shows the calculated lattice constants and valence stabilities for the Sm pnictides and chalcogenides 61,62 . Specifically, the total energy difference is calculated for the scenarios of trivalent and divalent rare earth ions.…”
Section: Sm Monopnictides and Monochalcogenidesmentioning
confidence: 99%
“…The theoretical description of Sm and Eu compounds is a challenge due to the 4f -electrons. The electronic structures of SmX [X = N, P, As, Sb, Bi, O, S, Se, Te, Po] compounds were calculated using the self--interaction corrected local-spin density approximation (LSDA) [7]. Recently, the electronic structure and optical spectra of SmS, SmSe, SmTe were calculated with the LSDA+U approach [8].…”
Section: Introductionmentioning
confidence: 99%